Medicinal Flora of Chhattisgarh - A Review - Jadhav, Dinesh (Indian Forester, 2013)
Chhattisgarh is known to harbour a rich wealth of medicinal plants. An attempt has been made to prepare a detailed account of medicinal flora of Chhattisgarh.The paper deals with 292 species of medicinal plants belonging to 240 genera and 88 families from Chhattisgarh. The information has been gathered from available literature on medicinal plants.